Exploration of Anammox-based deammonification and phosphorus recovery systems using biomolecular tools - Turpin, DeeAnn-Rose G., author; Carlson, Kenneth H., advisor; De Long, Susan K., committee member; Catton, Kimberly B., committee member; Kipper, Matthew J., committee member (Colorado State University. Libraries, 2018)
To view the abstract, please see the full text of the document.
Keywords: biomolecular tools; nitrogen removal; wastewater treatment; MBBR; anammox; phosphorus recovery